Pengaruh Jalan Kaki dan Senam Kaki terhadap Kadar Glukosa Darah Penderita Diabetes Melitus Tipe 2 - Hikmasari, Anisa; , Yulisna Mutia Sari, SSt.FT., M.Sc () (2016)
Background: Type 2 Diabetes Mellitus is a metabolic disease due to insulin action can not effective thus leading to high blood glucose levels. Therefore, it takes effort to control blood glucose levels, one of the them by doing walk or feet gymnastic exercise. Purpose: To know the effect of walking and feet gymnastic exercise to blood glucose levels of people with type 2 diabetes mellitus. Methods: Types of this research is quasi experiment. Research design is Pretest and Posttest Two Groups Design. The first group was given walking exercise and second group was given feet gymnastic exercise. Number of subjects is 20 people with purposive sampling technique which uses inclusion and exclusion criteria. Subjects were made to do exercise for 4 weeks with a frequency of 3 times/weeks. Result: Based on the result of wilcoxon test in acute effect (pre and post exercise) obtained p value of walking exercise = 0,005, p value of feet gymnastic exercise = 0,005. While chronic effects (pre and post of 4 weeks exercise) obtained p value of walking exercise = 0,092, p value of feet gymnastic exercise = 0,24. From mann whitney test obtained p value of acute effect = 1,000 and p value of chronic effect = 0,85. Conclusions: There is a significant acute effect between pre and post walking and feet gymnastic exercise, there is not chronic effect between pre and post walking and feet gymnastic exercise, and there is not significant difference of acute and chronic effect between walking and feet gymnastic exercise to blood glucose level of people with type 2 diabetes mellitus. Keywords: Blood Glucose Levels, Feet Gymnastic Exercise, Type 2 Diabetes Mellitus, Walking Exercise.